CD14(+)S100A9(+) Monocytic Myeloid-derived Suppressor Cells and Their Clinical Relevance in Non–Small Cell Lung Cancer - Feng, Po-Hao (American Thoracic Society, 2012)
Rationale: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous family of myeloid cells that suppress T-cell immunity in tumor-bearing hosts. Their clinical relevance remains unclear. Objectives: To identify subtypes of myeloid-derived suppressor cells in patients with non–small cell lung cancer (NSCLC) and their clinical relevance. Methods: CD11b(+)CD14(−) and CD11b(+)CD14(+) cells, determined and phenotyped by fluorescence-activated cell sorter analysis, in the peripheral blood mononuclear cells (PBMCs) of treatment-naive patients with advanced NSCLC were correlated with clinical data. T-cell activation in response to CD3/CD28 costimulation was determined by carboxy-fluorescein diacetate succinimidyl ester (CFSE) staining and ELISA analysis of IFN-γ. The percentage of CD11b(+)CD14(+)S100A9(+) cells in PBMCs was correlated with and tested as a predictor for treatment response in a cohort of patients prospectively receiving first-line cisplatin-based chemotherapy. Measurements and Main Results: Patients with NSCLC had a significantly higher ratio of CD11b(+)CD14(+) cells than healthy subjects, which was correlated with poor performance status and poor response to chemotherapy. The depletion of these cells in the PBMC reversed the suppression of CD8(+) and CD4(+) T cells. Isolated CD11b(+)CD14(+) cells suppressed CD8(+) T-cell proliferation and IFN-γ production, and the former effect was attenuated by the inducible nitric oxide synthase (iNOS) inhibitor aminoguanidine hydrochloride, arginase inhibitor N-hydroxy-nor-l-arginine (nor-NOHA), and blocking antibodies for IL-4Rα(+) and IL-10. CD11b(+)CD14(+) cells were monocyte-like, expressing CD33(+), CD15(−/low), IL-4Rα(+), and S100A9(+) and producing iNOS, arginase, and several cytokines. The ratio of S100A9(+) cells positively correlated with the suppressive ability of the CD11b(+)CD14(+) cells, was associated with poor response to chemotherapy, and predicted shorter progression-free survival. Conclusions: CD14(+)S100A9(+) inflammatory monocytes in patients with NSCLC are a distinct subset of MDSCs, which suppress T cells by arginase, iNOS, and the IL-13/IL-4Rα axis. The amount of these inflammatory monocytes is associated with poor response to chemotherapy. Clinical trial registered with www.clinicaltrials.gov (NCT 01204307).